An Ancient Respiratory System in the Widespread Sedimentary Archaea Thermoprofundales. (1st October 2022) - Zhang, Xinxu; Huang, Yuhan; Liu, Yang; Xu, Wei; Pan, Jie; Zheng, Xiaowei; Du, Huan; Zhang, Cuijing; Lu, Zhongyi; Zou, Dayu; Liu, Zongbao; Cai, Mingwei; et al.
Abstract: Thermoprofundales, formerly Marine Benthic Group D (MBG-D), is a ubiquitous archaeal lineage found in sedimentary environments worldwide. However, its taxonomic classification, metabolic pathways, and evolutionary history are largely unexplored because of its uncultivability and limited number of sequenced genomes. In this study, phylogenomic analysis and average amino acid identity values of a collection of 146 Thermoprofundales genomes revealed five Thermoprofundales subgroups (A–E) with distinct habitat preferences. Most of the microorganisms from Subgroups B and D were thermophiles inhabiting hydrothermal vents and hot spring sediments, whereas those from Subgroup E were adapted to surface environments where sunlight is available. H2 production may be featured in Thermoprofundales as evidenced by a gene cluster encoding the ancient membrane-bound hydrogenase (MBH) complex. Interestingly, a unique structure separating the MBH gene cluster into two modular units was observed exclusively in the genomes of Subgroup E, which included a peripheral arm encoding the [NiFe] hydrogenase domain and a membrane arm encoding the Na + /H + antiporter domain. These two modular structures were confirmed to function independently by detecting the H2 -evolving activity in vitro and salt tolerance to 0.2 M NaCl in vivo, respectively. The peripheral arm of Subgroup E resembles the proposed common ancestral respiratory complex of modern respiratory systems, which plays a key role in the early evolution of life. In addition, molecular dating analysis revealed that Thermoprofundales is an early emerging archaeal lineage among the extant MBH-containing microorganisms, indicating new insights into the evolution of this ubiquitous archaea lineage.